2023
DOI: 10.1038/s41420-023-01561-4
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from neural progenitor cells promote functional recovery after stroke in mice with pharmacological inhibition of neurogenesis

Abstract: Neural progenitor cells (NPCs) of the subventricular zone proliferate in response to ischemic stroke in the adult mouse brain. Newly generated cells have been considered to influence recovery following a stroke. However, the mechanism underlying such protection is a matter of active study since it has been thought that proliferating NPCs mediate their protective effects by secreting soluble factors that promote recovery rather than neuronal replacement in the ischemic penumbra. We tested the hypothesis that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…In our results, it was found that eND-EVs had neural proteins like Doublecortin, Neuropilin-1, Semaphorin-7a and also eND-EVs were preferentially taken up by neuron-like cells. Therefore, these findings closely align with and expand upon the work of Campero-Romero et al, who showed that NPC-derived EVs carried neural proteins and they are involved in many neural functions [47]. Moreover, the detection of neural proteins in eND-EVs in our results correlates with Gao et al's findings that NPC-derived EVs carried neural proteins such as growth factors [51].…”
Section: Acknowledgementssupporting
confidence: 92%
See 1 more Smart Citation
“…In our results, it was found that eND-EVs had neural proteins like Doublecortin, Neuropilin-1, Semaphorin-7a and also eND-EVs were preferentially taken up by neuron-like cells. Therefore, these findings closely align with and expand upon the work of Campero-Romero et al, who showed that NPC-derived EVs carried neural proteins and they are involved in many neural functions [47]. Moreover, the detection of neural proteins in eND-EVs in our results correlates with Gao et al's findings that NPC-derived EVs carried neural proteins such as growth factors [51].…”
Section: Acknowledgementssupporting
confidence: 92%
“…Adult neural progenitor cells are associated with maintaining and repairing the central nervous system, explaining the presence of such protein markers [45,46]. Besides, there are studies in the literature on proteomic analysis of neural progenitor cellsderived EVs (NPC-EVs) [47]. In the studies, it was stated that NPC-EVs take part in not only some neural functions but also neural progenitor-related proteins such as Teneurin-4 and Semaphorin-6 A, which are present in the NPC-EVs.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Therapeutics targeting NPC survival, such as cyclosporin A, have been shown to improve stroke outcomes [13][14][15]. Studies suggest that surviving NPCs can differentiate to replace dying neurons or provide trophic support after injury [11,16,17]. Hence, therapies that target downstream effector caspase-3 and caspase-7 have the potential to improve NPC survival in the brain, both in their periventricular niche as well as in the cortical stroke injury site.…”
Section: Introductionmentioning
confidence: 99%
“…We then conducted a study using primary cortical neurons subjected to oxygen–glucose deprivation (OGD), which was induced by exposing the cells to a glucose-free DMEM medium (Gibco) in a hypoxia chamber with a 100% N 2 atmosphere for 2 h as previously reported. 25 The lack of oxygen and energetic resources triggers an alteration at a morphological and functional level. This results in the failure of multiple neuronal actions, such as cell communication, and the progressive disruption of neuronal projections including axons and dendrites, compromising cell surveillance.…”
mentioning
confidence: 99%